Late-Variscan emplacement and genesis of the Vieira do Minho composite pluton, Central Iberian Zone: Constraints from U-Pb zircon geochronology, AMS data and Sr-Nd-O isotope geochemistry - Helena C B Martins (2013)
In the Central Iberian Zone synorogenic (syn- and late-D-3, the last deformation phase) composite batholiths of biotite-rich granitods with peraluminous character are well represented. We report here U-Pb zircon and monazite ages, geochemical, Sr-Nd-O isotopic data and Anisotropy of Magnetic Susceptibility (AMS) studies for the late-D-3 Vieira do Minho pluton, in northern Portugal. AMS reveals the paramagnetic behaviour of these granites and the magnetic fabric enhances the major role of NW-SE regional anisotropies on controlling the ascent and emplacement of the magmas. Magnetic anisotropy and medium temperature microstructures also point out the evolution of regional tectonics during crystallization of the magma. U-Pb zircon and monazite analyses yield consistent ages of 310 +/- 2 Ma and 312 +/- 2 Ma, interpreted as emplacement age. The Vieira do Minho pluton consists of two peraluminous monzogranites, the VMG and the MRG. Both have similar epsilon(Nd) values (VMG= -52 to -5.7; MRG= -4.98 to -5.96) but the VMG is slightly enriched in Sr-87/(86)(i)=0.7087-0.7098 as well as in delta O-18 in the range of 10.6 parts per thousand to 11.0 parts per thousand than the MRG with Sr-87/(86)(i)=0.7064-0.7075 and delta O-18=9.9 parts per thousand-10.5 parts per thousand. These granites are associated with coeval scarce grabroic intrusions and/or mafic microgranular enclaves which are not considered as mafic precursors of the associated granitic magmatism. Instead, a lower metaigneous crustal source, at different levels, is proposed based on the available data set.